G383(P) 8 high impact interventions: a regional survey of trainee experience. (25th October 2020) - Aguirre, D; Steadman, S; O'Keeffe, M; Kenyon-Blair, D; Cooper, H; Negrine, R; Goodyear, H; ,
Abstract : Aims: To explore local trainees' experience, identify emerging themes, good practice examples and make key regional recommendations. Method: A voluntary questionnaire was designed based on the '8 High Impact Actions to Improve the Working Environment for Junior Doctors' document by NHS Improvement. This was circulated on paper at trainees' regional teaching days and online via Survey Monkey from December 2018-March 2019. Results: 143/306 (47%) trainees responded. Conclusions: Our survey demonstrated local good practice examples. Implementation of our recommendations with School Board Support will improve junior doctors' working conditions as outlined by NHS improvement.